Penanaman Akhlak Melalui Pembiasaan Agama Islam Dalam Mencegah Penyimpangan Perilaku Siswa Kelas Vi Di Sd Negeri Kudu 01 Baki Sukoharjo - Wahyuni, Siswi Ina Sri, Dra. Hj. Sri Hartini, SH., M.Pd (2017)
The objectives of the research are: a) to describe the form of deviation of class VI student behavior, b) factors ausing deviation of student behavior of class VI, c) role of eacher in preventing deviation of student behavior of class VI, d) implementation of Islamic religion habitation prevent iation of class VI student behavior. Type of qualitative research. Data sources are principals, teachers, and students. Data collection techniques with observation, rviewandcumentation. The validity of the data using source and method angulation. Technical data analysis includes data reduction, data presentation and conclusions. The results of the study show that: a) The form of deviation of class VI student behavior such as 1) rebel (against teacher, dare to teacher) 2) dirty talk (say ndas, cangkeme), 3) make fun of friends (mock friends, dispute). B) Factors that affect the deviant behavior of 1) family and economic factors (lack of parental attention), 2) the environment (seen from people who behave badly), 3) association (often hanging out with unfavorable friends), 4) media Mass (such as internet, online games). C) The role of teachers in preventing behavioral aberrations such as 1) inculcating faith, 2) worship, 3) instill morals to students. D) Implementation of Islamic religion bituation include 1) the habitation of the creed in it invites students to read juz'ama and give spiritual splash, 2) praying worship invites students to pray and 3) moral habitation invites students to work conscientious school environment. Implementation of Islamic religious practice is quite effective.